Political Celebrity and Communication Style Joko Widodo on New Media - Lidwina Mutia Sadasri (BBPSDMP KOMINFO MAKASSAR, 2019)
A Celebrity as a person who is being worshipped, not only originated from an artist, such as musician, actor or actress that starring any movie but also could originate from the political context. President Joko Widodo (Jokowi) as a leader of the Republic of Indonesia is one of the celebrity examples with his massive narration on new media. Jokowi has a Facebook page and its content related to his activities. The content could be seen from communication perspectives as a manifestation of celebrity image. In the context of Presidential Election in 2019, the emergence of the content on Jokowi Facebook Page also could be understood as one platform that is used by his fans or public to gather some information in relation with a presidential candidate. This research is conducted using content analysis using QDA Miner in April 2018. This study resulting from that communication style that Jokowi is using tend to be setting the agenda’s function, policy issue’s topic, referential/neutral’s register, and storytelling’s stagecraft.